The Transparency Paradox: Why Transparency Alone will not Improve Campaign Regulations. Issue 4 (25th July 2020) - Power, Sam
Abstract: The role of new sources of data has become of increasing interest to those involved in political campaigning and a legislative focus of policy makers and regulators. Utilising Karl‐Heinz Nassmacher's 'magic quadrangle' of 'accounting, practicality, sanctions and transparency' and a case study of the Political Parties, Elections and Referendums Act 2000 this article unpicks how successful the 'guiding philosophy' of transparency was in delivering increased citizen confidence in the democratic process. I ultimately argue that at the heart of all discussions about what regulation in this area should look like, an uncomfortable paradox has to be accepted: that transparency may well help to quell actual instances of malfeasance and the misuse of data, but may at the same time increase citizen distrust in democratic processes. Any regulation should consider the ways in which transparency might be implemented such that it better supports the stated legislative aims.